PUTUSAN TATA USAHA NEGARA YANG MEMILIKI KEKUATAN EKSEKUTORIAL TIDAK DIPATUHI OLEH PEJABAT TATA USAHA NEGARA - Pattipawae, Dezonda Rosiana (Jurnal Saniri, 2020)
The weak implementation of State Administrative Court Decisions is due to the absence of an executive institution and force to force in the implementation of State Administrative Court Decisions, so that the implementation of State Administrative Court Decisions depends on the awareness and initiative of the State Administration Officer. Article 116 paragraph (4) and paragraph (5) of Law Number 51 of 2009 concerning Second Amendment to Law Number 5 of 1986 concerning State Administrative Court, namely the imposition of sanctions for State Administration Officers who do not implement a decision that has the power permanent law in the form of forced payment of money (dwangsom) and/or administrative sanctions and publication in print media. Article 116 paragraph (6) concerning the Second Amendment to Law Number 5 of 1986 concerning State Administrative Court, besides the efforts stipulated in the previous law, also regulates reporting of disobedience of the State Administration Officer to implement the decision of the Administrative Court The country said to the President as the holder of the highest governmental authority and to the people's representative institutions to carry out the oversight function.